2016
DOI: 10.3892/mco.2016.918
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of hyperthermic intraperitoneal chemotherapy for gastric cancer with peritoneal metastasis

Abstract: Abstract. Peritoneal metastasis (PM) is a poor prognostic factor in patients with gastric cancer. The aim of this study was to evaluate the efficacy and safety of hyperthermic intraperitoneal chemotherapy (HIPEC) in patients with advanced gastric cancer with PM by retrospective analysis. A total of 54 gastric cancer patients with positive ascitic fluid cytology were included in this study: 23 patients were treated with systemic chemotherapy combined with HIPEC (HIPEC+ group) and 31 received systemic chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…HIPEC, combining regional hyperthermia and IPC after CRS, has been applied to treat PC and is the most effective and recommended treatment option for appendiceal mucinous cancer and pseudomyxoma peritonei (20). For a number of malignancies that present with PC, including peritoneal mesothelioma (21), and gastric (22), colorectal (23) and pancreatic (24) cancer, CRS and HIPEC prolonged long-term survival in selected patients. Some oncology centres, encouraged by the promising results of HIPEC in the treatment of PC of gastrointestinal origin, have shifted this method as a treatment option to patients with advanced EOC (25).…”
Section: Discussionmentioning
confidence: 99%
“…HIPEC, combining regional hyperthermia and IPC after CRS, has been applied to treat PC and is the most effective and recommended treatment option for appendiceal mucinous cancer and pseudomyxoma peritonei (20). For a number of malignancies that present with PC, including peritoneal mesothelioma (21), and gastric (22), colorectal (23) and pancreatic (24) cancer, CRS and HIPEC prolonged long-term survival in selected patients. Some oncology centres, encouraged by the promising results of HIPEC in the treatment of PC of gastrointestinal origin, have shifted this method as a treatment option to patients with advanced EOC (25).…”
Section: Discussionmentioning
confidence: 99%
“…A significant challenge for GC treatment is the absence of early diagnostic biomarkers (6). Yuan et al (7), reported that the 5-year survival rate of early GC is ~30-fold high compared with that of late-stage GC. A number of studies have identified aberrantly expressed miRNAs in GC, which serve regulatory roles in tumors (8).…”
Section: Introductionmentioning
confidence: 99%
“…The HIPEC population had decreased gastric cancer-related symptoms than those receiving chemotherapy alone, particularly the presence of malignant ascites was reduced. 16 Similarly, in studies by Facchiano et al, 65 and Yarema et al, 25 they showed that, as well as providing survival benefit associated with CRS-HIPEC, HIPEC alone caused complete clinical regression of the symptoms of malignant ascites in patients with primary gastric cancer with PC. Remarkably, evidence for palliation of malignant ascites via HIPEC had already been described by the late 1990s.…”
mentioning
confidence: 99%
“…In a retrospective study, Yuan et al 16 showed that, when compared with traditional chemotherapy, HIPEC increases both survival and improves quality of life. The HIPEC population had decreased gastric cancer-related symptoms than those receiving chemotherapy alone, particularly the presence of malignant ascites was reduced.…”
mentioning
confidence: 99%
See 1 more Smart Citation